Implementasi Total Quality Management dalam Meningkatkan Mutu Pendidik (Studi Kasus di SMP Islam Terpadu Misykat Al-Anwar Kwaron, Jombang) - Laily Masruroh; Haris Supratno (Menara Tebuireng, 2017)
School or education institution, as place of education process that can be implemented by dynamic and complex system. The main activity of school is human resource management. Quality human resources preparation can be reached only by education quality. All of education system component must complete main standard quality. The organization can increase and endure its quality by build system of increasing quality. Once of them is TQM (Total Quality Management). TQM based on satisfaction as main target. Customers can be different to internal and external customer. In education, internal is manager of education management, such as school principle, teachers, staff, and school operator. The focuses of this research are: (1) Teacher quality in SMP Misykat Al-Anwar Kwaron, Jombang, (2) Implementation TQM on increasing teacher quality in SMP Misykat Al-Anwar Kwaron, Jombang, (3) Supporter and resistor factors of implementation TQM on increasing teacher quality in SMP Misykat Al-Anwar Kwaron, Jombang. The researcher uses field research method (qualitative descriptive). The technique of data collecting uses observation, interview, discussion, and documentation. In this research, have discovered that teacher quality at SMP Misykat Al-Anwar Kwaron Jombang, is teacher who have elected and selected well. To know the teacher professionalism can be looked through education grade, certification, and training education program, and teacher competent test. Implementation of TQM in increasing teacher quality through teacher recruitment, so teacher have elected and selected are teacher who have skills and creativities. Quality improvement in SMP Misykat Al-Anwar Kwaron Jombang can be implemented by consultation, building, workshop, seminar, and teacher training. The supporter factors of implementation TQM on increasing teacher quality is influenced by external and internal factors. To real this matter, school principle create good job condition by protect togetherness inter group, give opportunity to express opinion, give motivation and build work spirit to concern commitment which have decided, so activities can continue well